2015
DOI: 10.1002/ccd.26345
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter aortic valve replacement versus surgical aortic valve replacement in patients with cirrhosis

Abstract: TAVR could be a viable option for aortic valve replacement in cirrhosis patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 16 publications
3
29
2
Order By: Relevance
“…This method uses lower priming volume, reduced foreign surface area, and interdisciplinary preoperative and postoperative treatment. Contrarily, reported mortality after TAVR in these patients is lower than that of SAVR, and ranges from 0 to 10% . Our study confirms these findings, and found similar lower in‐hospital mortality among patients with TAVR and SAVR.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…This method uses lower priming volume, reduced foreign surface area, and interdisciplinary preoperative and postoperative treatment. Contrarily, reported mortality after TAVR in these patients is lower than that of SAVR, and ranges from 0 to 10% . Our study confirms these findings, and found similar lower in‐hospital mortality among patients with TAVR and SAVR.…”
Section: Discussionsupporting
confidence: 88%
“…Data on postoperative blood transfusion and PPM implantation specific to SAVR in cirrhotic patients are very limited . Due to widespread availability, expanded indications, and early favorable observational data on TAVR in the patients with cirrhosis, it is increasingly used to treat severe AS patients, in consideration of shorter length of stay and less procedural complications . Our data support findings from the previous small studies.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Hepatology evaluation suggested very high surgical risk due to chronic liver disease. Thus, she was referred for TAVR in the face of high surgical risk [7,8].…”
Section: Case Presentationmentioning
confidence: 99%